2008
DOI: 10.1016/j.prostaglandins.2007.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid actions on PGHS-1 and -2 cyclooxygenase kinetics

Abstract: Cyclooxygenase (COX) catalysis by prostaglandin H synthase (PGHS) is a key control step for regulation of prostanoid biosynthesis. Both PGHS isoforms are integral membrane proteins and their substrate fatty acids readily partition into membranes, but the impact of phospholipids and lipid membranes on COX catalysis and the actions of COX inhibitors are not well understood. We have characterized the COX kinetics and ibuprofen inhibition of the purified PGHS isoforms in the presence of phosphatidylcholine (PC) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Considering the first hypothesis, the critical micelle concentration (CMC) lies in the range of 6-60 μM for most unsaturated fatty acids, depending on pH and the counter-cation used (31)(32)(33)(34), which is consistent with the inflection point of 20 μM (Fig. 2A).…”
Section: Resultssupporting
confidence: 69%
“…Considering the first hypothesis, the critical micelle concentration (CMC) lies in the range of 6-60 μM for most unsaturated fatty acids, depending on pH and the counter-cation used (31)(32)(33)(34), which is consistent with the inflection point of 20 μM (Fig. 2A).…”
Section: Resultssupporting
confidence: 69%
“…The K M value for hPGHS-1 is about four-fold higher than that observed for oPGHS-1 [39]. This is probably due to the higher level of detergent used in the present assays, as increasing detergent concentration is known to increase the cyclooxygenase K M value [40]. Mutation of Tyr504 to phenylalanine resulted in a 24% decrease in cyclooxygenase specific activity, a smaller change than seen for the analogous mutation in hPGHS-2 [22], but did not change significantly the K M value for arachidonate (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, in artificial lipid membrane systems, such as liposome vesicles, fatty acids and NSAIDs become sequestered in the large vesicles, subsequently limiting their movement into the enzyme active site and subsequent availability for catalysis and inhibition. As a consequence, the measured kinetic parameters become altered, making data interpretation challenging (18). In contrast to liposome vesicles, nanodisc incorporation confines COX-2 to a much smaller patch of lipid membrane such that substrates and inhibitors that enter the lipid bilayer are immediately localized in close proximity to the entrance of the cyclooxygenase channel.…”
Section: Discussionmentioning
confidence: 99%
“…Rand Doyen and colleagues characterized the kinetics of COX-1 and COX-2 in the presence of phosphatidylcholine molecules of varying acyl chain lengths and physical state (18). These studies revealed that monomeric, micelle, and bilayer forms of phospholipids exhibit an inhibitory effect on cyclooxygenase catalysis, predominantly due to sequestration of substrate (18). MirAfzali and colleagues successfully incorporated COX-1 and COX-2 into large unilamellar vesicles produced from a mixture of DOPC:DOPS that had been doped with oleic acid (19).…”
mentioning
confidence: 99%